Traditions of Eloquence : The Jesuits and Modern Rhetorical Studies - O'Malley, John, S.J; Brereton, John C., 1943-; Gannett, Cinthia, 1959- (Book collections on Project MUSE., 2016)
This groundbreaking collection explore the important ways Jesuits have employed rhetoric, the ancient art of persuasion and the current art of communications, from the sixteenth century to the present. Much of the history of how Jesuit traditions contributed to the development of rhetorical theory and pedagogy has been lost, effaced, or dispersed. As a result, those interested in Jesuit education and higher education in the United States, as well as scholars and teachers of rhetoric, are often unaware of this living 450-year-old tradition. Written by highly regarded scholars of rhetoric, composition, education, philosophy, and history, many based at Jesuit colleges and universities, the essays in this volume explore the tradition of Jesuit rhetorical education - that is, constructing "a more usable past" and a viable future for eloquentia perfecta, the Jesuits' chief aim for the liberal arts. Intended to foster eloquence across the curriculum and into the world beyond, Jesuit rhetoric integrates intellectual rigor, broad knowledge, civic action, and spiritual discernment as the chief goals of the educational experience. -- from back cover.